Non-Coding RNAs at the Gnas and Snrpn-Ube3a Imprinted Gene Loci and Their Involvement in Hereditary Disorders - Plagge, Antonius (Frontiers in Genetics, 2012)
Non-coding RNAs (ncRNAs) have long been recognized at imprinted gene loci and provided early paradigms, to investigate their functions and molecular mechanisms of action. The characteristic feature of imprinted genes, their monoallelic, parental-origin-dependent expression, is achieved through complex epigenetic regulation, which is modulated by ncRNAs. This minireview focuses on two imprinted gene clusters, in which changes in ncRNA expression contribute to human disorders. At the GNAS locus loss of NESP RNA can cause autosomal dominant Pseudohypoparathyroidism type 1b (AD-PHP-Ib), while at the SNRPN-UBE3A locus a long ncRNA and processed snoRNAs play a role in Angelman-Syndrome (AS) and Prader-Willi-Syndrome (PWS). The ncRNAs silence overlapping protein-coding transcripts in sense or anti-sense orientation through changes in histone modifications as well as DNA methylation at CpG-rich sequence motifs. Their epigenetic modulatory functions are required in early development in the pre-implantation embryo or already in the parental germ cells. However, it remains unclear whether the sequence homology-carrying ncRNA itself is required, or whether the process of its transcription through other promoters causes the silencing effect.